Limitations of Follow-Up Procedures in Campaign Fund Report Audits - Salsabila, Vania; Hidajat, R. Sjarief (Universitas Indo Global Mandiri Palembang, 2024)
Campaign funds used in elections can come from political parties, the personal wealth of legislative candidates, and donations. The receipt of campaign funds must undergo an audit process to ensure the validity of contributions received by political parties. This study aims to validate the limitations of follow-up audit procedures in the audit of campaign fund reports related to donation confirmations. The research method used is qualitative, with data collection methods including observation, interviews, and documentation studies. The results of the study indicate that auditors still face difficulties and limitations in auditing campaign fund reports concerning donations. These limitations are exacerbated by the absence of follow-up procedures established by the KPU as the policymaker to provide guidelines on follow-up procedures in response to campaign fund donation confirmations.